A Rare Case Presentation of HbE/ Î² Thalassemia - Singh, Anu; Kumar, Vijay; Singh, Meetu; Sahu, Priya; Baweja, Garima; Marwah, Sadhna (Annals of Pathology and Laboratory Medicine, 2020)
HbE/Î² thalassemia (HbE/Î² thal) genotype accounts for approximately one half of severe Î² thalassemia cases worldwide. The disorder shows marked clinical variability ranging from mild asymptomatic anemia to life threatening disease. Here, we report a case of a 2-year-old boy from Bihar presenting with severe haemolytic jaundice. Complete haematological profile and Haemoglobin High Performance Liquid Chromatography (Hb HPLC) using Biorad version was done of the patient along with the family was done to arrive at the diagnosis of this rare hemoglobinopathy.